Synthesis and crystal structures of [Ph3PCH2PPh3]I2 dichloromethane disolvate and [Ph3PCH2PPh3](BI4)2 - Ganguly, Rakesh (2017)
Reaction of BI3 with carbodiphosphorane, C(PPh3)2, gives a mixture of the dicationic compounds, methylenebis(triphenylphosphonium) diiodide dichloromethane disolvate, C37H32P22+·2I−·2CH2Cl2 or [Ph3PCH2PPh3]I2·2CH2Cl2 (I), methylenebis(triphenylphosphonium) bis(tetraiodoborate), C37H32P22+·2BI4− or [Ph3PCH2PPh3](BI4)2 (II). Solvents are the source of the protons at the ylidic C atom. The P—C—P angle is 124.1 (2)° for (I) and 121.7 (3)° for (II), while the two P—C bond lengths are 1.804 (4) and 1.807 (5) Å in (I), and 1.817 (5) and 1.829 (5) Å in (II). In the crystal of (I), the protons of the central P—CH2—P C atom exhibit weak C—H...I hydrogen bonds with the respective anions. The anions in turn are linked to the dichloromethane solvent molecules by C—H...I hydrogen bonds. In the crystal of (II), one of the BI4− anions is linked to a phenyl H atom via a weak C—H...I hydrogen bond.